PERTUMBUHAN DAN MORFOLOGI AKAR KELAPA SAWIT (Elaeis guinensis Jacq.) PADA SALINITAS GENANGAN BERBEDA - Erick Firmansyah (Program Studi Agroteknologi INSTIPER, 2017)
Palm oil can experience high salinity waterlogging at the same place and time; however, the effects of these two conditions on growth and morphology of palm oil root was not fully understood. Research has been done by combining two levels of salinity (high salinity and low salinity) and three levels of waterlogging (without waterlogging, twoweek waterlogging intervals, and four-week waterlogging intervals). The study was conducted in pots for 4 months used 4 months old oil palm planting material. The results show that high salinity and waterlogging consistently decrease the oil palm root growth parameter. Longer duration of waterlogging decreases root growth greater than shorter waterlogging. High salinity and waterlogging do not consistently change the ratio of the area of each primary, secondary, and tertiary root tissue. Palm oil forms pneumatophore and aerenchyma under both non saline and saline waterlogging. High salinity followed by waterlogging can compensate the negative effects of salt ions (Na+ and Cl– ) through morphological adaptations, changes in ion absorption rate, and root membrane impermeability. Keywords : Morphology, Palm oil, Root, Salinity, Waterlogging